RELATIONSHIP BETWEEN TEACHERS PERSONALITY COMPETENCE AND PRINCIPAL SUPERVISION AGAINTS STUDENT WITH RELIGIOUS AWARENESS PERCEPTION - Rahayu, Neneng (Tawazun: Jurnal Pendidikan Islam, 2019)
One of the problems in our society is the low moral and adolescent personal ability. That happens because of the low closeness of teens with Allah. Teenager religious awareness is a potential that have tendency to develop. One of the factors that influence the development of the religious awareness is the school environment, where there are elements namely teachers and school principals. Teachers is one of the pillars of education in achieving educational goals. IRE teachers is one of which becoming a model for students to emulate and emulated its Islamic personal ability. Students also viewed togetherness of principals in Islamic learning activities. With the IRE teacher's personality and good supervision by principals, is expected to grow student’s religious awareness. Data processing was performed using SPSS Windows series 20. Personality of IRE teachers and school principal’s supervision according to the perceptions of students with student’s religious awareness being mediumly correlated, linear and significant. Data from a double regeresi analysis showed that 29.1% of student’s religious awareness may be affected jointly by IRE teacher’s personality variables and supervising school principal. While 70.9% are influenced by other factors.